DAMPAK MOTIVASI PESERTA DIDIK PADA POKOK BAHASAN LARUTAN ELEKTROLIT DAN NON ELEKTROLIT TERHDAP HASIL BELAJAR SECARA DARING DI KELAS X IPA SMA NEGERI ORANSBARI - Lenci Anggur Sineri; Ramlah Ramlah (Arfak Chem: Chemistry Education Journal, 2020)
AbstractThis research is entitled "Students' Learning Motivation in Electrolyte and Non-Electrolyte Solution Subjects Class X IPA SMA Negeri Oransbari, South Manokwari Regency Using Online Learning on Cognitive Learning Outcomes During the COVID-19 Pandemic". The purpose of this study was to determine whether there is a relationship between the learning motivation of class X science students at SMA Negeri Oransbari, South Manokwari Regency with online learning on cognitive learning outcomes during the COVID-19 pandemic and to find out what percentage (%) the effect of learning motivation on class X students. IPA SMA Negeri Oransbari, South Manokwari Regency with online learning on cognitive learning outcomes during the COVID-19 pandemic. The results of this study indicate that there is a relationship or correlation between student learning motivation and cognitive learning outcomes using online learning with an R value of 0.159 and there is an influence between student motivation and cognitive learning outcomes using online learning with an effect of 25%. Keywords: Cognitive Learning Outcomes, Electrolyte and Non-Electrolyte Solutions, Student Learning Motivation, COVID-19 Pandemic Period and Online Learning